Health care in Jamaica : quality, outcomes, and labor supply - Lavy, Victor, 1949- 1949- (LSMS working paper, 1995)
"Investigates relationships among labor force participation, health outcomes, and quality of health care in Jamaica. Develops an econometric model linking demand for health care, health status outcomes, and labor force participation"--Handbook of Latin American Studies, v. 57